Prognostic Impact of Early Treatment and Oxaliplatin Discontinuation in Patients With Stage III Colon Cancer: An ACCENT/IDEA Pooled Analysis of 11 Adjuvant Trials. Issue 4 (1st February 2023) - Gallois, Claire; Shi, Qian; Meyers, Jeffrey P.; Iveson, Timothy; Alberts, Steven R.; de Gramont, Aimery; Sobrero, Alberto F.; Haller, Daniel G.; Oki, Eiji; Shields, Anthony Frank; Goldberg, Richard M.; Kerr, Rachel; et al.
Abstract : PURPOSE: Oxaliplatin-based adjuvant chemotherapy in patients with stage III colon cancer (CC) for 6 months remains a standard in high-risk stage III patients. Data are lacking as to whether early discontinuation of all treatment (ETD) or early discontinuation of oxaliplatin (EOD) could worsen the prognosis. MATERIALS AND METHODS: We studied the prognostic impact of ETD and EOD in patients with stage III CC from the ACCENT/IDEA databases, where patients were planned to receive 6 months of infusional fluorouracil, leucovorin, and oxaliplatin or capecitabine plus oxaliplatin. ETD was defined as discontinuation of treatment and EOD as discontinuation of oxaliplatin only before patients had received a maximum of 75% of planned cycles. Association between ETD/EOD and overall survival and disease-free survival (DFS) were assessed by Cox models adjusted for established prognostic factors. RESULTS: Analysis of ETD and EOD included 10, 447 (20.9% with ETD) and 7, 243 (18.8% with EOD) patients, respectively. Compared with patients without ETD or EOD, patients with ETD or EOD were statistically more likely to be women, with Eastern Cooperative Oncology Group performance status ≥ 1, and for ETD, older with a lower body mass index. In multivariable analyses, ETD was associated with a decrease in disease-free survival and overall survival (hazard ratio [HR], 1.61, P < .001 and HR, 1.73, P < .001), which was not the case for EOD (HR, 1.07, P = .3 and HR, 1.13, P = .1). However, patients who received < 50% of the planned cycles of oxaliplatin had poorer outcomes. CONCLUSION: In patients treated with 6 months of oxaliplatin-based chemotherapy for stage III CC, ETD was associated with poorer oncologic outcomes. However, this was not the case for EOD. These data favor discontinuing oxaliplatin while continuing fluoropyrimidine in individuals with significant neurotoxicity having received > 50% of the planned 6-month chemotherapy.